Assessment of the quality factor of tribosystems and relationship with tribological characteristics - Vojtov, V.A.; Voitov, A.V. (Problems of Tribology, 2020)
The definition of the quality factor of the tribosystem has been further developed, which, unlike the known one, takes into account not only the geometric dimensions of the tribosystem, thermal diffusivity of triboelement materials, lubricating medium and deformation propagation rate in the surface layers of the material, but also the function of changing the rheological properties of the surface layers of materials during running-in and their increase during running-in. Theoretical studies have established that three parameters have the maximum effect on the quality factor: sliding speed, roughness of friction surfaces and lubricating medium. Experimental studies have established the relationship between the value of the quality factor, wear rate and coefficient of friction during steady-state operation of tribosystems. It has been shown that an increase in the figure of quality factor reduces the above parameters, and the criterion itself Qmax is a measure of the potential of the tribosystem adapt to the operating conditions